Zinc enhances autophagic flux and lysosomal function through transcription factor EB activation and V-ATPase assembly - Kim, Ki-Ryeong; Park, Sang Eun; Hong, Ji-Ye; Koh, Jae-Young; Cho, Dong-Hyung; Hwang, Jung Jin; Kim, Yang-Hee (Frontiers in Cellular Neuroscience, 2022)
The stimulation of autophagy or lysosomes has been considered therapeutic for neurodegenerative disorders because the accumulation of misfolded proteins is commonly observed in the brains of individuals with these diseases. Although zinc is known to play critical roles in the functions of lysosomes and autophagy, the mechanism behind this regulatory relationship remains unclear. Therefore, in this study, we examined which mechanism is involved in zinc-mediated activation of autophagy and lysosome. Exposure to zinc at a sub-lethal concentration increased autophagic vesicles and rescued autophagy arrested by chloroquine (CQ) or ammonium chloride, autophagy inhibitors. Zinc alleviated mRFP-GFP-LC3 puncta and p62 accumulated by CQ in both H4 glioma and mouse cerebrocortical cultures. Zinc also rapidly induced the expression of cathepsin B (CTSB) and cathepsin D (CTSD), representative lysosomal proteases, which appeared likely to be mediated by transcription factor EB (TFEB). We observed the translocation of TFEB from neurite to nucleus and the dephosphorylation of TFEB by zinc. The addition of cycloheximide, a chemical inhibitor of protein synthesis, inhibited the activity of CTSB and CTSD at 8 h after zinc exposure but not at 1 h, indicating that only late lysosomal activation was dependent on the synthesis of CTSB and CTSD proteins. At the very early time point, the activation of cathepsins was mediated by the increase of assembly of V-ATPase on lysosomes and resultant lysosomal acidification. Finally, we presented that protein aggregation and the blocking of autophagy by mutant P301L tau were relieved by zinc in SK-N-BE(2)-C cells overexpressing P301L mutant tau. Zinc was more effective than rapamycin at inducing TFEB-dependent CTSB and CTSD expression and V-ATPase-dependent lysosomal acidification and activation of CTSB/CTSD. These results suggest that the regulation of zinc homeostasis could be a new approach for developing treatments of neurodegenerative diseases, including Alzheimer’s and Parkinson’s.